Non-fluent/Agrammatic Variant of Primary Progressive Aphasia With Generalized Auditory Agnosia - Watanabe, Hiroyuki; Ikeda, Manabu; Mori, Etsuro (Frontiers in Neurology, 2020)
Cortical neurodegeneration-induced non-fluent/agrammatic variant of primary progressive aphasia (nfvPPA) is a clinical syndrome characterized by non-fluent speech, such as apraxia of speech or agrammatism. We describe the case of an 80-year-old right-handed woman who exhibited nfvPPA. Atypically, our patient also presented with generalized auditory agnosia. Brain magnetic resonance imaging revealed left-sided predominant atrophy of the bilateral perisylvian area, including the inferior frontal and superior temporal lobes. In a series of auditory tasks assessing generalized auditory agnosia, our patient was unable to accurately identify verbal sounds, environmental sounds, or familiar Japanese songs that she could sing. In the context of recent studies, our study indicates the existence of a clinical syndrome characterized by progressive speech disorder with auditory agnosia. This case report thus provides novel insights into the spectrum of language impairment induced by neurodegenerative disease.